Estudio del impacto turístico del malecón y la ruta del rio del cantón Quevedo, año 2015 - Tapia Ortiz, Livington (2015)
The Canton Quevedo has many recreational spaces , it has encouraged private enterprise and one public , the latter who must ensure the benefits of social, with the firm intention to comply with the provisions of the Constitution of the Republic, that regional governments must meet the needs of the people in service . With regard to tourism, it is important to emphasize that the progress of peoples is due to the quality of its management , in these cases sectional governments and private enterprise willingness to be a fundamental part of socio-economic development , and thus create a climate of sustainable innovation that may occur in the medium term, thereby meeting the needs of the public with this differentiated service to the market. In the present investigation the constant need for such ideas, which will allow innovation and effective activation of tourist processes such as social impact in the area of study, taking into account key factors such as geographical location, reflects the strategic location , nature, and secondly the management of resources by regional governments, which to strengthen tourism must make agreements with private companies in order to meet the objectives. The research was based on the application of technical instruments applied to the target population in order to appreciate their concerns and needs of a differentiated service in the market, as they visit the boardwalk 70% and 76% of the river route once a week, with a segment of ages ranging from 18 to 25 years with 44% of the target audience, this activity is carried out in the morning on the route of the river with 68% and overnight boardwalk with 70%, resulting in an advantage competitive in the service of tourism in Canton. And, the degree of preference of the public study of these sites is 47% visit it with their families, especially the banks of the river in both the seawall and the route, stating the need to promote open house (open house ) and tour boats with a response rate of 21% and 26% in boardwalk path of the river, which potencializaría active tourism in Canton Quevedo and therefore would be at the top of Mind (first recall) of mind consumer of tourist services. This paper covers basic criteria and concepts, in which the elements of importance to study the impact of tourism on the boardwalk and path of the river are summarized as inherent methods to the problems they were designed, which once analyzed contributed to issue the respective Document findings and recommendations based on the study conducted